Cattle influence on the population structure of yerba mate (Ilex paraguariensis) in araucaria forest Influência do gado na estrutura populacional de erva-mate (Ilex paraguariensis) em floresta com araucárias - Stedille L.I.B.* (2019)
© 2019, Universidade Federal de Santa Maria. All rights reserved.This study characterized the demography and spatial pattern of a yerba mate (Ilex paraguariensis A.St.-Hil) population covering areas with different use histories (Presence and Absence of Cattle) in a Araucaria Forest. Data collection was performed in three ha, half in each area. The frequency of individuals by height, spatial distribution pattern, diameter distribution (for reproductive individuals) and sexual ratio were evaluated. An inverted “J” pattern predominated, being exclusive to an area with Cattle Presence, a place which presented a lower density of individuals. The predominant spatial distribution pattern was aggregated, and the reproductive individuals have a preferentially random pattern at the shortest distances. Results indicated that cattle presence changes the density of I. paraguariensis individuals and the proportion of individuals in the evaluated demographic classes.